2019
DOI: 10.1039/c9gc00289h
|View full text |Cite
|
Sign up to set email alerts
|

Uncatalyzed, on water oxygenative cleavage of inert C–N bond with concomitant 8,7-amino shift in 8-aminoquinoline derivatives

Abstract: Oxygenative cleavage of an inert CAr–NH2 bond with concomitant 1,2 amine migration in 8-aminoquinoline derivatives is achieved through an efficient, catalyst free, one step synthesis of 8-benzyloxy, 7-aminoquinoline directly from 8-aminoquinoline in water at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…[24] Henry-Ritter reactions are reported to access one pot synthesis of N-(β-Nitro) amides from aldehyde, nitro compounds and nitriles. [25] In continuation of our research efforts to explore CÀ H functionalisation reactions for the construction of CÀ C, [26,27] CÀ N [28,29] and CÀ O [30,31] bonds in open flask conditions, we aimed to investigate the one-pot multicomponent reaction for the synthesis of amides. Considering the importance of the complex amide products, we assumed that readily available and less expensive nitriles would be an excellent amidation tool in tandem Ritter reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Henry-Ritter reactions are reported to access one pot synthesis of N-(β-Nitro) amides from aldehyde, nitro compounds and nitriles. [25] In continuation of our research efforts to explore CÀ H functionalisation reactions for the construction of CÀ C, [26,27] CÀ N [28,29] and CÀ O [30,31] bonds in open flask conditions, we aimed to investigate the one-pot multicomponent reaction for the synthesis of amides. Considering the importance of the complex amide products, we assumed that readily available and less expensive nitriles would be an excellent amidation tool in tandem Ritter reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[31] J. Zhou et al reported a catalytic Ritter reaction of 3-alkyl and 3-aryl-3-hydroxy oxindoles and nitriles for the synthesis of 3-substituted-3-aminooxindoles (Figure 2). [32] As a part of our ongoing research program on CÀ H functionalizations for the construction of CÀ C [33,34,35] and CÀ N [36,37,38,39] bonds, we became interested in Ritter and Mannich reactions and envisioned that multicomponent Ritter reaction could affect the single step synthesis of diverse and complex 2oxindole derivatives by C3 functionalization of isatin. In this paper, we report the development of novel and efficient acid catalyzed synthesis of variety of sterically crowded diamide products, 3-aryl-3'-amidooxindoles in one pot MCR directly from commercially available isatin, nucleophile, and nitrile (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Neat water or so called “ on‐water ” reaction was first introduced by Sharpless . Since then many elegant reactions have been reported . Although on‐water reactions offer much benefits, wide‐spread adoption has been limited by inability of on‐water reaction to be adapted to all traditional chemical transformation reactions due to heterogeneous behaviour.…”
Section: Introductionmentioning
confidence: 99%